2022
DOI: 10.9734/csji/2022/v31i230276
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition, Bioactive Potential, and Thermal Behaviour of Cyperus scariosus Essential Oil

Abstract: Plant derived oils have recently been found to be more effective in pharmaceutical sectors than synthetic goods since these plants contain physiologically active chemicals with a wide range of therapeutic effects. Essential oil, also known as essence, volatile oil, etheric oil, or aetheroleum, is a complex mixture of volatile elements biosynthesised by living organisms, which is particularly abundant in aromatic plants. This research summarizes facts on the chemistry of essential oil isolated from Cyperus scar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
0
3
1
Order By: Relevance
“…The EO from rhizomes of C. scariosus is used as an ingredient in several Ayurvedic formulations as an anti-infective agent [55]. Previous studies have reported the growthinhibitory effect of C. scariosus EO against carbapenem-resistant Klebsiella pneumoniae and methicillin-resistant S. aureus in liquid media [56]. In our study, we have observed only weak antibacterial activity of the EO.…”
Section: Discussioncontrasting
confidence: 45%
“…The EO from rhizomes of C. scariosus is used as an ingredient in several Ayurvedic formulations as an anti-infective agent [55]. Previous studies have reported the growthinhibitory effect of C. scariosus EO against carbapenem-resistant Klebsiella pneumoniae and methicillin-resistant S. aureus in liquid media [56]. In our study, we have observed only weak antibacterial activity of the EO.…”
Section: Discussioncontrasting
confidence: 45%
“…The EO from rhizomes of C. scariosus is used as an ingredient in several Ayurvedic formulations as an anti-infective agent [ 55 ]. Previous studies have reported the growth-inhibitory effect of C. scariosus EO against carbapenem-resistant Klebsiella pneumoniae and methicillin-resistant S. aureus in liquid media [ 56 ]. In our study, we have observed only weak antibacterial activity of the EO.…”
Section: Discussionmentioning
confidence: 99%
“…The essential oil was extracted from the bark of the plant. The bark was crushed and then subjected to hydro-distillation with distilled water for 24 hours using a Clevenger apparatus [19]. The essential oil was separated from the hydrosol water using a separatory funnel, and the hydrosol water was recycled into the flask containing the boiling plant material.…”
Section: Sample Collection and Extraction Of Essential Oilmentioning
confidence: 99%
“…The impacts of other essential oils that contain ketone or esters, like myrcene, thujone, or geranyl acetate, are much weaker. It has been revealed that the terpenoids in EOs impede the enzymatic processes of energy metabolism [9]. Notably, Cinnamomum cassia has been identified as plants possessing antibacterial and antifungal properties.…”
Section: Introductionmentioning
confidence: 99%